The twenty-first-century media industry : economic and managerial implications in the age of new media - Hendricks, John Allen (Lanham, Md. : Lexington Books, 2010)
""The Twenty-First-Century Media Industry is well worth reading not only for its broad scope but also for the timeliness of the chapters. Readers will come away with a clear conceptual map of the changing media landscape as well as a detailed understanding of the challenges of the years ahead in forging a new business model, or set of business models, for media operating in the digital age."---John V. Pavlik, Rutgers University" "The Twenty-First-Century Media Industry provides an intriguing examination into the role that new media technologies are having on the traditional media industry from a media management perspective. Consumers' behaviors and expectations are being shaped by new media technologies. They now expect information on demand and on the go as well as at their fingertips via the Internet. In order to stay relevant and competitive, traditional media managers and practitioners are developing new business models and new business philosophies. The volume contributors explore the business strategies being implemented by some media industries, such as newspapers, mobile phones, cinema, broadcasting, and the recording industry, which are struggling not only to remain competitive and profitable but simply to survive. The Twenty-First-Century Media Industry will be a valuable resource for those scholars interested in the emerging role of new media technologies and the new media industry as it evolves in the twenty-first century"--BOOK JACKET.
Change: technology, economic implications, and consumer behaviors. New media: new technology, new ideas or new headaches / Suzy Smith and John Allen Hendricks -- Media management: the changing media industry and adaptability / Mary Jackson Pitts and Lily Zeng -- DVRs and the empowered audience: a transformative new media technology takes off / James R. Walker and Robert Bellamy -- The obstinate audience revisited: the decline of network advertising / Douglas A. Ferguson -- Going viral: mass media meets innovation / Joan Van Tassel -- Implications of new media technologies. The first domino: the recorded music industry and new technology / Robert Bellamy and Robert Gross -- Changes and challenges in the print industry: the new landscape of the print media / Steven Phipps -- Challenges and opportunities, new models, and the emergence of the next newsroom / Jen McClure -- Broadcast and cable on the third screen: moving television content to mobile devices / Jennifer Meadows -- How to reach the masses: broadcasters' uses of the Internet and cell phones / Maria Williams-Hawkins -- Making money with mobile / Maria Williams-Hawkins -- Cinema in the age of RWX culture / Alexander Cohen -- Local market radio: programming and operations in a new media world / Tony R. DeMars.
Includes bibliographical references (p. 269-277) and index.
Keywords: Mass media -- Technological innovations; Digital media -- Economic aspects; Digital media -- Social aspects; Management; ICT